VD_FINDINFO Jug / 2019 / 419 vom 23. Mai 2019 - VD Tribunal cantonal (2019)
DIFFAMATION, APPRÉCIATION DES PREUVES, PROCÈS ÉQUITABLE, PRINCIPE DE L'ACCUSATION, PUBLICATIONEN GÉNÉRAL, DOMMAGES-INTÉRÊTS | 41 CO, 173 CP, 68 CP, 115 al. 1 CPP (CH), 3 al. 2 let. c CPP (CH), 9 CPP (CH)